PENGEMBANGAN APLIKASI LAYANAN BAGIAN UMUM (ALBUM 2.0) DALAM PENGELOLAAN BARANG MILIK NEGARA PADA DIREKTORAT JENDERAL HAK ASASI MANUSIA - Rachman, Hasyim; Musyafi, Ayatulloh Michael; Nasution, Hafifah; Sasmi, Aji Ahmadi (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2024)
This research aims to design the development of an information management system for State-Owned Goods (Barang Milik Negara) within government agencies as an effort to optimize internal supervision functions over the implementation of information systems and digitize the management process of State-Owned Goods. This research focuses on the Secretariat of the General Affairs Division of the Directorate General of Human Rights as the research object because the information system implemented by the General Affairs Division, namely the General Affairs Service Application (ALBUM), has problems based on the problem analysis and needs assessment conducted. This study uses Research and Development (R&D) design with the ADDIE model. The development phase is limited to the Design stage, involving the creation of Data Flow Diagrams (DFD) and User Interface designs using CANVA and FIGMA as tools to assist in the design development process. Based on the analysis results, there is a need for information system development in the General Affairs Service Application (ALBUM) in the aspect of internal service. The internal services that can be developed include the Inventory Items feature by adding a display for additional requested items, and the second development is the addition of a loan feature for State-Owned Goods. The design development aligns with the problem analysis and the needs derived from the information obtained. It is expected that the development carried out will optimize the internal supervision function over the implementation of the General Affairs Service Application (ALBUM) information system and in every aspect of the State-Owned Goods management process